Application of Infrared Reflectance Spectroscopy on Plastics in Cultural Heritage Collections: A Comparative Assessment of Two Portable Mid-Fourier Transform Infrared Reflection Devices. Issue 7 (July 2021) - Angelin, Eva Mariasole; de Sá, Susana França; Soares, Inês; Callapez, Maria Elvira; Ferreira, Joana Lia; Melo, Maria João; Bacci, Mauro; Picollo, Marcello
Plastics have been increasingly used to create modern and contemporary art and design, and nowadays, museum collections hold numerous objects completely or partially made of plastics. However, the preservation of these materials is still a challenging task in heritage conservation, especially because some plastics show signs of degradation shortly after their production. In addition, different degradation mechanisms can often take place depending on the plastic composition and appropriate environmental and packaging conditions should be adopted. Therefore, methods for in situ and rapid characterization of plastic artifacts' composition are greatly needed to outline proper conservation strategies. Infrared (IR) spectroscopy, such as attenuated total reflection Fourier transform infrared spectroscopy (ATR FT-IR), is a well-established method for polymeric material analysis. However, ATR FT-IR requires an intimate contact with the object, which makes its application less appropriate for the in situ investigation of fragile or brittle degraded plastic objects. Mid-FT-IR reflectance spectroscopy may represent a valid alternative as it allows in situ measurements with minimum or even no contact, and IR data can be acquired rapidly. On the other hand, spectral interpretation of reflectance spectra is usually difficult as IR bands may appear distorted with significant changes in band maximum, shape, and relative intensity, depending on the optical properties and surface texture of the material analyzed. Presently, mid-FT-IR reflection devices working in external reflection (ER FT-IR) and diffuse reflection infrared Fourier transform spectroscopy (DRIFTS) modes have been used in cultural heritage research studies. As the collected vibrational information depends on the optical layout of the measuring system, differences between ER FT-IR and DRIFT spectra are thus expected when the same polymer is analyzed. So far, ER FT-IR and DRIFT spectroscopy have been individually explored for the identification of plastic objects, but comparative studies between the application of two reflectance FT-IR modes have not been presented yet. In this work, the use of two portable FT-IR spectrometers equipped with ER FT-IR and DRIFTS modes were compared for plastics identification purposes for the first time. Both references of polymeric materials and historical plastic objects (from a Portuguese private collection) were studied and the differences between ER FT-IR and DRIFT spectra were discussed. The spectra features were examined considering the two different optical geometries and analytes' properties. This new insight can support a better understanding of both vibrational information acquired and practical aspects in the application of the ER FT-IR and DRIFTS in plastic analysis. Graphical Abstract